HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN KEPUASAN PASIEN DI RUANG RAWAT INAP IRINA A RSUP PROF. DR. R. D. KANDOU MANADO (JURNAL KEPERAWATAN, 2014)
Abstract: Background The nurse is a profession focused on the care of individuals families and communities to achieve optimal health conducted by nurses by increasing mutual trust and helping to solve problems with communication, where the nurse can listen the client's problems and explain the procedure of nursing actions, it would disturb therapeutic relation which impact patient dissatisfaction if it is unimplemented. Objective this study aims to analyze the relation of the nurse therapeutic communication with patient satisfaction in Inpatient Unit Irina A of RSUP Prof. Dr. R. D. Kandou Manado. Method of research is an analytic survey with cross sectional approach. The technique of collecting sampling was done through purposive sampling. There were 67 respondents, it indicated that 42 people (91,3%) were satisfied that the therapeutic communication skills both nurses and patients, and 4 people (8.7%) were less satisfied . For the therapeutic communication skills which were good enough and 5 patients (23.8%) felt satisfy and 16 patients (76.2%) felt less satisfy. Results of bivariate chi square obtained p value 0.000 (pv